2015
DOI: 10.1063/1.4928316
|View full text |Cite
|
Sign up to set email alerts
|

Crack propagation in graphene

Abstract: Temperature and strain-rate dependent fracture strength of grapheneThe crack initiation and growth mechanisms in an 2D graphene lattice structure are studied based on molecular dynamics simulations. Crack growth in an initial edge crack model in the arm-chair and the zig-zag lattice configurations of graphene are considered. Influence of the time steps on the post yielding behaviour of graphene is studied. Based on the results, a time step of 0.1 fs is recommended for consistent and accurate simulation of crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…1(a). The atom to atom interactions of carbon in Graphene are modeled based on the Tersoff potential [49], which has been successfully applied to predict mechanical properties of Graphene [9,52,50,10,68]. Variation of the fracture strength with the cut-off distance (r c ) at 0 K is plotted in Fig.…”
Section: Modelling and Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…1(a). The atom to atom interactions of carbon in Graphene are modeled based on the Tersoff potential [49], which has been successfully applied to predict mechanical properties of Graphene [9,52,50,10,68]. Variation of the fracture strength with the cut-off distance (r c ) at 0 K is plotted in Fig.…”
Section: Modelling and Simulationsmentioning
confidence: 99%
“…The equations of motion and the time integration is carried out based on the Verlet algorithm [48]. The effect of numerical stability has been investigated in [10]. Budarapu et al [10] have reported that 1.0 fs is sufficient to study the mechanical behavior of Graphene up to yielding.…”
Section: Modelling and Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational methods have been very helpful for bridging the scales from atoms to microstructures and for predicting structure-property relationships [6]. For graphene, several atomistic studies -mostly based on classical molecular dynamics (MD) simulations -of crack propagation have been performed to extract elastic properties and fracture toughness [7,8,9,10,11,12,13,14]. Only recently, the latter was measured using in situ tensile testing of suspended graphene [15].…”
Section: Introductionmentioning
confidence: 99%